2007
DOI: 10.2139/ssrn.950344
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of Volatility Functionals in the Simultaneous Presence of Microstructure Noise and Jumps

Abstract: We propose a new concept of modulated bipower variation for diffusion models with microstructure noise. We show that this method provides simple estimates for such important quantities as integrated volatility or integrated quarticity. Under mild conditions the consistency of modulated bipower variation is proven. Under further assumptions we prove stable convergence of our estimates with the optimal rate n −1/4 . Moreover, we construct estimates which are robust to finite activity jumps.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
81
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(83 citation statements)
references
References 42 publications
(36 reference statements)
2
81
0
Order By: Relevance
“…This idea is widely adopted in various extensions. See , Podolskij and Vetter (2009), Christensen et al (2010Christensen et al ( , 2017, Andersen et al (2012), Christensen and Podolskij (2012), Barunik and Vacha (2015), and Mykland and Zhang (2017), etc. (2) The truncation method (Mancini, 2008(Mancini, , 2011, which discards relatively large returns in RV summation terms, and 755 variables.…”
Section: Introductionmentioning
confidence: 99%
“…This idea is widely adopted in various extensions. See , Podolskij and Vetter (2009), Christensen et al (2010Christensen et al ( , 2017, Andersen et al (2012), Christensen and Podolskij (2012), Barunik and Vacha (2015), and Mykland and Zhang (2017), etc. (2) The truncation method (Mancini, 2008(Mancini, , 2011, which discards relatively large returns in RV summation terms, and 755 variables.…”
Section: Introductionmentioning
confidence: 99%
“…In the context of volatility estimation, several methods to de-noise the data have been proposed. Widely used methods include the two-scale method ), the multi-scale method (Zhang (2006)), the realized kernel method (Barndorff-Nielsen, Hansen, Lunde, and Shephard (2008)), the pre-averaging method (Jacod, Li, Mykland, Podolskij, and Vetter (2009) and Podolskij and Vetter (2009)), and the quasi-maximum likelihood method (Xiu (2010)). These methods are shown to be effective when the noise is an additive white noise, or admits some kind of independence between successive observations.…”
Section: Introductionmentioning
confidence: 99%
“…Then, we suggest a new optimal external random variable with a density that yields the second-order accuracy of the bootstrap. Gonçalves et al (2014) have shown that the wild bootstrap procedure applied on the nonoverlapping pre-averaged returns (as originally proposed by Podolskij and Vetter, 2009) estimates the asymptotic variance as well as the asymptotic mixed normal distribution of the pre-averaged realized volatility estimator. However, for this relatively simple statistic, we can simply use, for instance, the consistent variance estimator proposed by Podolskij and Vetter (2009).…”
Section: Introductionmentioning
confidence: 99%
“…Gonçalves et al (2014) have shown that the wild bootstrap procedure applied on the nonoverlapping pre-averaged returns (as originally proposed by Podolskij and Vetter, 2009) estimates the asymptotic variance as well as the asymptotic mixed normal distribution of the pre-averaged realized volatility estimator. However, for this relatively simple statistic, we can simply use, for instance, the consistent variance estimator proposed by Podolskij and Vetter (2009). Hence, the additional effort required for the bootstrap is justified if the resulting approximation to the distribution of the statistic is better than the one relying on the asymptotic normality.…”
Section: Introductionmentioning
confidence: 99%